2013
DOI: 10.4073/csr.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

Educational and Skills‐Based Interventions for Preventing Relationship and Dating Violence in Adolescents and Young Adults: A Systematic Review

Abstract: The Campbell Collaboration (C2) was founded on the principle that systematic reviews on the effects of interventions will inform and help improve policy and services. C2 offers editorial and methodological support to review authors throughout the process of producing a systematic review. A number of C2's editors, librarians, methodologists and external peerreviewers contribute. The Campbell Collaboration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 108 publications
1
24
0
2
Order By: Relevance
“…Programs should be appropriately tailored to the culture and needs of target audiences (Fellmeth et al, 2013;Whitaker et al, 2006) Assessment of student needs to help, develop, and refine effective curricula and ensure sustained change along with process evaluation (Gavine et al, 2016). Specific population-targeted in-depth programs could be more efficient than universal programs (Cassidy & Matzopoulos, 2016;Gavine et al, 2016).…”
Section: Overall Recommendationsmentioning
confidence: 99%
“…Programs should be appropriately tailored to the culture and needs of target audiences (Fellmeth et al, 2013;Whitaker et al, 2006) Assessment of student needs to help, develop, and refine effective curricula and ensure sustained change along with process evaluation (Gavine et al, 2016). Specific population-targeted in-depth programs could be more efficient than universal programs (Cassidy & Matzopoulos, 2016;Gavine et al, 2016).…”
Section: Overall Recommendationsmentioning
confidence: 99%
“…Reason for exclusion Barlow, smailagic, Ferriter, Bennett, and Jones (2010) too few school-based studies on outcomes of interest included Baskin et al (2010) Unclear if outcomes of interest were included in review, and if they were to what extent Beelmann and Raabe (2009) Review of reviews Protocol of a review, not an actual review Bowman-Perrott, Burke, nan, and Zaini (2014) too few school-based studies on outcomes of interest included candelaria, Fedewa, and ahn (2012) could not clearly determine all of the studies which were school-based and which considered outcomes of interest cobb, sample, Morgen, and Johns (2006) could not clearly determine all of the studies which were school-based and which considered outcomes of interest edwards and hinsz (2014) too few school-based studies on outcomes of interest included ehiri, hitchcock, ejere, and Mytton (2007) Protocol of a review, not an actual review Fellmeth, heffernan, nurse, habibula, and sethi (2013) could not clearly determine which studies that were included in analysis were school-based Ferguson, Miguel, Kilburn, and sanchez (2007) effects for bullying and other types of violence were not reported separately. could not determine extent to which violence outside of bullying was represented in statistics grove, evans, Pastor, and Mack (2008) could not clearly determine how many school-based interventions were included, and thus how represented they were in the statistics R. hahn et al (2007) a published version of this report was also found in our searches and thus used instead.…”
Section: Appendix B References Of Included Reviewsmentioning
confidence: 99%
“…Around 30% of adolescents, both boys and girls, are or have been involved in DV, although moderate forms of violence are more frequent than severe forms [6]. Psychological DV victimization is also most prevalent among young people (aged [14][15][16][17][18][19][20], with rates of up to 94% in girls and 93% in boys, while physical DV may affect up to 42% of girls and 39% of boys [7] There are several research studies regarding how DV affects the health outcomes of the adolescent population and its impact on adult lifestyles. Over the short term, victims and perpetrators of IPV tend to report lower rates of self-esteem and more feelings of self-blame, hurt, anxiety and anger.…”
Section: Introductionmentioning
confidence: 99%
“…However, these prevention strategies have not been strong enough to decrease the incidence of DV. Thus, it is necessary to conduct studies to determine how these interventions affect adolescents' skills to prevent this problem [16].…”
Section: Introductionmentioning
confidence: 99%